GE_GERICHTE P/297/2017 vom 18. September 2017 - GE Cour de justice (2017)
MOTIVATION DE LA DÉCISION ; SURVEILLANCE DES TÉLÉCOMMUNICATIONS ; SURVEILLANCE(EN GÉNÉRAL) ; SOUPÇON | CPP.269; CPP.270; CPP.279; CPP.282; CPP.283